Perception of poisonous medicinal plants based on their names (as exemplified by the Polish and Russian nomenclature) - Stec, Wanda (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
Botanical names reflect how people perceive, interpret, and categorize the world of plants from the linguistic point of view. The article aims to demonstrate how the image of plants that are poisonous and, at the same time, used in medicinal treatment is shaped by their denomination. The author analyzes the motivations for nomenclature on the examples of common and folk names in Polish and Russian, against the background of the international Latin botanical nomenclature. In the process of linguistic nomination of poisonous medicinal plants, the criteria which are taken into account are both objective, based on knowledge, observation, and experience, as well as subjective, based on evaluation and associations. The names do not always reflect the plants’ harmful impact on people because their remaining properties might have prevailed during the linguistic nomination process.